Stone Barrington: Indecent Exposure - Book 42 - Woods, Stuart (New York : G.P. Putnam's Sons, 2017)
"Trouble always seems to find Stone Barrington, but with his debonair charm, unflappable composure, and cunning foresight, he always gets his man (and his lady....)"--
Publishers Weekly
Library Journal Prepub Alert
ONIX annotations
Adult.
Adult.
Keywords: Adventure fiction